THE USE ONLINE METACOGNITIVE STRATEGY ON READING STUDENTS' SKILLS - Mamluatul Ilmiyah (INCARE, International Journal of Educational Resources, 2020)
Metacognitive techniques are considered to be essential for developing reading skills. This research investigates whether there are major variations in student reading comprehension scores using metacognitive approaches techniques and investigates what metacognitive strategies are applied to students reading comprehension. Many of the participants in this study were high school eleventh-grade students. Data collection is carried out in the manner of the Reading Comprehension Test and Metacognitive Strategy Questionnaire. The findings showed that metacognitive strategies have a positive impact on student reading achievement. Based on the estimation of the eta-squared effect size of the paired sample, the t-test of the experimental community was 0.141. This indicates that there was a broad impact, with major changes in student grades before and after treatment. There are nine subcategories of metacognitive methods for student understanding. For example, Advance Organizer, Self-Management, Tracking Awareness, Output Monitoring, Self-Assessment Self-Assessment, and Self-Reflection. Although the applicability is strong Metacognitive techniques for reading comprehension fall into two subcategories: Selective treatment and organizational preparation. And the most significant use of the method is Selective focus, though self-reflection is the least technique. Keywords : online metacognitive, metacognotive strategy, reading skills